Багатокритеріальна кластеризація вугільних шахт України на основі параметрів експлуатації - Хорольський А. О. (НТУ "ДП", 2026)
Здійснено кластерний аналіз діючих вугільних шахт України на основі параметрів експлуатації. Проаналізовано кількісні та якісні параметри експлуатації з метою визначення стратегічних кластерів. За допомогою методу ліктя і алгоритму k-середніх встановлено, що для наявних конфігурацій технологічних, гірничо-геологічних, економічних параметрів існує три кластери. A cluster analysis of active Ukrainian coal mines was conducted based on their operational parameters. Both quantitative and qualitative operational variables were analyzed to identify strategic clusters. Using the elbow method and the k-means algorithm, it was determined that three distinct clusters exist for the current configurations of technological, geological, and economic parameters. An optimal strategy for the completion of industrial reserves can be defined for each cluster.
Multicriteria clustering of Ukrainian coal mines based on operational parameters
Keywords: кластер; алгоритм k-середніх; метод ліктя; параметр; стратегія; оптимізація.; cluster; k-means algorithm; elbow method; parameter; strategy; optimization.